The Analysis of Green Accounting Cost Impact on Corporations Financial Performance - Riyadh, Hosam Alden; Al-Shmam, Maher A.; Huang, Henry Hongren; Gunawan, Barbara; Alfaiza, Salsabila Aisyah (International Journal of Energy Economics and Policy, 2020)
This research aimed to analyze the Green Accounting (GA) impact on financial performance (FP). The research question pertaining to this research will answer empirical investigation and analysis in the top 100 multinationals corporations. The research seeks to answer the questions: Does green accounting cost have an impact on financial performance in the top 100 multinationals corporations? Thus, secondary data and multiple regression analysis were employed in this research, such as CSR reports, sustainability reports, and financial statements. The selected corporations were 100 largest multinational corporations in the year 2018. Then, the green accounting used a proxy of the environmental cost (EC), while financial performance employed a proxy of Return on Capital Employed (ROCE). The finding of autonomous Green Accounting costs on financial performance has a negative relationship. Keywords: Green Accounting, Environmental Cost, and Financial Performance JEL Classifications: Ðž14, D24, Ð¡41 DOI: https://doi.org/10.32479/ijeep.9238